SONG AND MOVEMENT AS MEDIA OF EARLY CHILDHOOD LANGUAGE DEVELOPMENT - Warananingtyas Palupi; Ruli Hafidah; Karsono Karsono (Universitas Sebelas Maret, 2019)
The early childhood learning should cover many aspects of development, ranging from religious and moral values, social, emotional, cognitive, physical motor, linguistic and artistic. Song and Movement are still identified with motion. Early childhood learning is synonymous with singing, clapping and playing while active. Motion and song activities are very tightly attached and can not be separated, especially in providing learning to young children. Motion and song learning is an activity in playing while learning and learning through playing, so activities performed through motion/movement and song are expected to please the child as well as touch the development of language, sensitivity to the rhythm of music, motor development, confidence, and the courage to take risks. Through motion or movement and song, children learn to develop their linguistic ability, it is through listening song dan music rhythm, children develop their receptive ability in language. And children’ expressive ability in language is developed while children sing the song. Therefore, it is necessary for an activity that can train early childhood educators in giving stimulation to children through motion and song.